Supporting Lesotho's Economic Diversification and Trade Integration : Structural Transformation through Greater Export Competitiveness - Arenas, Guillermo (World Bank, Washington, DC, 2018)
This report provides a multifaceted diagnostic overview of Lesotho's export competitiveness, including an analysis of the macroeconomic environment in which exporters and importers operate in Lesotho; level, growth, composition, and market share performance of Lesotho's exports; the evolution of FDI inflows and their sectoral composition; the diversification of products and markets, as well as the quality and sophistication of Lesotho's exports. It builds on this with CGE analysis of potential impacts based on specific trade-related scenarios as well as diagnostic tools to facilitate the analysis of global and regional value chain participation and integration. The report then formulates several recommendations that could enhance export competitiveness, deepen Lesotho's integration in global and regional value chains in goods and services and strengthen the country’s ability to respond to changing external environment.